Pharmacokinetics, Pharmacodynamic Efficacy Prediction Indexes and Monte Carlo Simulations of Enrofloxacin Hydrochloride Against Bacterial Strains That Induce Common Clinical Diseases in Broiler Chickens - Bonassa, Karina P. D.; Miragliotta, Miwa Y.; Simas, Rosineide C.; Eberlin, Marcos N.; Anadón, Arturo; Moreno, Ronilson A.; Reyes, Felix G. R. (Frontiers in Veterinary Science, 2021)
Pharmacokinetic parameters and efficacy prediction indexes (Cmax/MIC90 and AUC0-24/MIC90) of an enrofloxacin hydrochloride (ENR-HCl) veterinary product soluble in water were determined in healthy broiler chickens of both sexes after a single oral dose of ENR-HCl (equivalent to 10 mg ENR base/kg bw). Monte Carlo simulations targeting Cmax/MIC90 = 10 and AUC0-24/MIC90 =125 were also performed based on a set of MIC (minimum inhibitory concentration) values of bacterial strains that induce common clinical diseases in broiler chickens and that showed to be susceptible to ENR-HCl. Plasma concentrations of ENR and ciprofloxacin (CIP) were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Plasma concentration-time curves were found to fit a noncompartmental open model. The ratio of the area under the plasma concentration-time curve (AUC) of CIP/ENR was 4.91%. Maximum plasma concentrations of 1.35 ± 0.15 µg/mL for ENR-HCl and 0.09 ± 0.01 µg/mL for CIP were reached at 4.00 ± 0.00 h and 3.44 ± 1.01 h, respectively. Areas under the plasma vs. time concentration curve in 24 h (AUC0–24) were 18.91 ± 1.91 h x µg/mL and 1.19 ± 0.12 h x µg/mL for ENR-HCl and CIP, respectively. Using a microbroth dilution method, the minimum inhibitory concentration (MIC90) values were determined for ENR-HCl for 10 bacterial strains (Mycoplasma gallisepticum, Mycoplasma synoviae, Avibacterium paragallinarum, Clostridium perfringens, Escherichia coli, Pseudomonas aeruginosa, Salmonella ser. Enteritidis, Salmonella ser. Gallinarum, Salmonella ser. Pullorum and Salmonella ser. Typhimurium), which are the most common causes of infectious clinical diseases in broiler chickens. The PK/PD efficacy prediction indexes and Monte Carlo simulations indicated that the ENR-HCl oral dose used in this study is useful for bacterial infections in treating C. perfringens (Gram-positive), E. coli and S. ser. Enteritidis (Gram-negative) and M. gallisepticum bacteria responsible for systemic infections in poultry, predicting a success rate of 100% when MIC ≤ 0.06 μg/mL for E. coli and S. ser. Enteritidis and MIC ≤0.1 μg/mL for M. gallisepticum. For C. perfringens, the success rate was 98.26% for MIC ≤ 0.12.. However, clinical trials are needed to confirm this recommendation.